ARQUEOLOGÍA DE LA CUENCA DEL RÍO MOLLEBAMBA, ANTABAMBA–APURÍMAC - Dalen Luna, Pieter van (2017)
This article presents the characteristics of prehistoric settlements on both banks of the river Mollebamba located in four rural communities that make up the district Juan Espinosa Medrano in the province of Antabamba. The settlements, belonging to different cultural periods, from preceramic sites to Tawantinsuyu, with a greater presence of Late Intermediate settlements. The information presented in this work is of great importance because they are the first archaeological history of this province so little investigated.